Speech Acts Analysis in Album Song’s Lyrics by Osen Hutasoit - Grace Siagian, Anselia; Nur Hadi, Muhammad; David Marudut Silalahi, Charles (Green Publisher Indonesia, 2025)
Songs are a combination of words and melodies that serve as a medium for expressing emotions and messages. This study examines the speech acts present in the lyrics of